Cognitive Behavior Therapy untuk mengurangi perilaku melukai diri pada kasus depresi - Esti Paramitayani (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Depression is a mood disorder characterized by the absence of hope, prolonged sadness, excessive feelings of helplessness, inability to make decisions, inability to concentrate, loss of enthusiasm for life, feelings of tension and a desire to end life or hurt oneself. The purpose of this study was to see whether self-injury behavior in depression could be reduced after giving Cognitive Behavioral Therapy. The subject is twenty-three years old woman; suffer from depression and often self-harm. The assessments used were clinical interviews, observation, Beck Depression Inventory, graphic tests, Wechsler Adult Intelligence Scale, Thematic Apperception Test, and WHODAS. Frequency self -injury behavior subject was  three times a week average. The intervention given is Cognitive Behavioral Therapy to reduce the frequency of self-injury by 10 sessions. The result shows that Cognitive Behavioral Therapy is effective in reducing self-injury behavior and can reduce negative thinking in people with depression.